An effectively enhanced vapor phase hybridized conductive polymer based on graphene oxide and glycerol influence for strain sensor applications. (9th November 2022) - Palicpic, Coleen M.; Khadka, Roshan; Yim, Jin-Heong
Abstract : An effectively enhanced graphene-based TPU-GPS-GLY based strain sensor was prepared by modifying TPU-GPS with the help of glycerol incorporation. An efficient method was shown for the significant improvement of the performance as a strain sensor. Abstract : The fabrication of a flexible and highly sensitive strain sensor with the incorporation of glycerol, by vapor phase hybridization, improves the physical properties of ternary composite elastomers consisting of thermoplastic polyurethane (TPU), graphene oxide, polyethylene glycol and silica (TPU-GPS). The addition of glycerol to the TPU-GPS composite improves the dispersion of graphene oxide and the mechanical, electrical, thermal, and strain sensing sensitivity properties of the graphene oxide-based strain sensor. A certain amount of glycerol in the composite blend is modified to achieve excellent strain sensor performance. The results revealed 65% strain increase compared to the TPU-GPS strain sensor on its elongation at break. The presence of glycerol in the polymer matrix is confirmed by field-emission scanning electron microscopy (FE-SEM), attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) characterization studies. More impressively, TPU-GPS with 3 wt% of glycerol (TPU-GPS-3GLY) demonstrates outstanding sensitivity (gauge factor = 20) that is two times higher than that of the TPU-GPS pristine composite. Furthermore, the sensor can monitor a small-scale strain up to <1% and respond for up to 20 000 cycles with extraordinary stability and repeatability. Owing to the uniform dispersion of graphene oxide in the polymer matrix as a result of glycerol introduction, the composite represents a useful development in the strain sensor application.